Atherosclerosis and wine - Kocmur, Bozidar Kocmur (Journal of Cardiovascular Medicine and Cardiology, 2024)
<span style="color: #333333; font-family: Merriweather, serif; font-size: 17px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">One of the most important risk factors for the origin and development of atherosclerosis is certainly excessive intake of fat in everyday nutrition. This risk factor, and the way it affects the origin and development of atherosclerosis, is described in the article “Atherosclerosis and lymph/risk factors”. In this article, based on verified and proven facts, it is suggested that the primary causes and initiators of atherosclerotic changes in the arterial system of the circulatory system are chylomicrons, especially large ones, which occur under the influence of several risk factors.